Taṭwīr al-Kitāb Ayo Belajar Bahasa Arab Bi Waraqah al-`Amal `Inda aṭ-Ṭullāb Li Tarqiyah Qudratihim `Alā Mahārah al-Kitābah (al-Baḥṡ Wa at-Taṭwīr Bi MIN 15 Pidie Jaya): (MIN 15 Pidie Jaya البحث والتطوير بـــ) بورقة العمل عند الطلاب لترقية قدرتهم على مهارة الكتابة Ayo Belajar Bahasa Arab تطوير كتاب - Muharramah Muharramah; Hilmi Hilmi; Azwir Azwir (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2022)
This thesis is entitled "Development Book “Ayo Belajar Bahasa Arab” with LKS to improve students writing skills in Writing Hijayyah Letters (R&D research at MIN 15 Pidie Jaya)". The researcher found the problem that about 60% of the third-grade students at MIN 15 Pidie Jaya were not able to write Hijaiyah letters correctly, there were even some of them who wrote from left to right, especially when they wrote continuous letters in sentences. Based on these problems, the researchers wanted to develop worksheets to help improve their ability to write Hijaiyah letters. The LKS that the researcher wants to develop is the procedure for writing separate Hijaiyah and Hijaiyah letters that are connected to train them in writing so that they can write Arabic words and sentences correctly. The purpose of this study was to determine student responses to the development of worksheets. And to determine the level of effectiveness of the LKS development that has been developed. This researcher uses the R&D (Research and Development) method with the research instruments used are student questionnaires, expert validation, and tests. And the researcher took 15 third-grade students as samples. As for the data analysis technique, the researcher used the T-test formula from the SPSS program. The results obtained based on this research are the development of worksheets based on valid expert assessments with a value of 93%, while the test results show that the use of worksheets is effective in improving their ability to write Hijaiyah letters. This is based on the results of the value of sig 0.00 <0.05.